Special characteristics of technological indicators of white aboriginal grape varieties - Shmigelskaya Natalia; Lutkov Igor; Maksimovskaya Victoria; Sivochoub Galina; Тimoshenko Ekaterina (BIO Web of Conferences, 2023)
Sparkling wines are high in demand, and they firmly occupy their strong position in wine market. In recent years, there was a reorientation of consumers from the low-price segment of sparkling wines to the mid-price and premium ones, motivating the manufacturer to be searching for new solutions for the unique high-quality wine production. One of the ways of its producing is the use of aboriginal grape varieties. At the same time, there is insufficient information about the distinctive technological characteristics of aboriginal grape varieties, which makes it difficult to release a product of high-quality. As a research result, significant indicators were established (the mass concentrations of titratable acids, proteins, polysaccharides, the content of phenolic substances in the must without contact with the pulp, the content of phenolic substances in the must after extraction of the pulp for 4 hours, the technological stock of phenolic substances) to differentiate grapes in accordance with the origin, and characterize their technological potential. A comparative analysis of aboriginal grape varieties with classical cultivars traditionally used in sparkling wine production was carried out. Deviations in the criterion technological indicators of aboriginal grape varieties were established to be taken into account when selecting grape processing technology for high-quality sparkling wine production.